RADIO TELESCOPE URAN-4 AND THE PROBLEM OF RADIO INTERFERENCE - Galanin, V. V.; Lytvynenko, O. A.; Derevyagin, V. G.; Kravetz, R. O. (Одеські астрономічні публікації, 2018)
The URAN-4 decameter radio telescope, which is located in thevillageofMayakiof theOdessaregion, is an element of system of the URAN radio telescopes (Ukrainian Radiointerferometer of theAcademyofSciences). The radio telescope is used according to the following scientific programs: measurements in the composition of the Interferometer with the Super Large Base (VLBI), to study the angular structure of discrete radio sources; the study of the nonstationarity of the flux of cosmic radio sources and the study of the influence of the space environment on the characteristics of the received signals. RT URAN-4 operates at frequencies of 10-30 MHz and consists of an antenna and an equipment complex. A telescope antenna is an electrically controlled phased array of 128 turnstile vibrators. It identifies two linear signal components and is endowed with the possibility of changing the position of the antenna pattern in space (2048 discrete positions of the beam). The geometric dimensions of the array238 meters(West-East direction) and28 meters(North-South direction). The size of the antenna pattern in the modulation mode of signal reception at a frequency of 25 MHz is 2.7 x 22 degrees. In the VLBI interferometer mode, a resolution of about 2 seconds of arc is realized. The instrumental complex of the RT URAN-4 is represented by two types of modulation radiometers, which make it possible to measure the flux densities of radio sources and apparatus intended for VLBB measurements. The working frequency range in which RT URAN-4 operates has a high level of radio interference. The work gives definitions of interference acting in the decameter range. Considered methods of dealing with them. One of the methods to combat interference is the work of the radio telescope on the frequencies permitted and legally protected from interference, the list of which is given in the article. The paper deals with issues related to the organization of the security zone around the radio telescope. On its territory, the maximum allowable power for existing nearby transmitting radio facilities and interfering industrial facilities should be legitimized, in the designated working lanes. At the same time, a monitoring service for the radio spectrum should be organized. The paper deals with the developed and manufactured portable direction finder. Its characteristics are given, recommendations on its use are given.